Time-resolved piezoelectric response in relaxor ferroelectric (Pb0.88La0.12)(Zr0.52Ti0.48)O3thin films - Rössle, Matthias; Thomas, Olivier; Mocuta, Cristian; Rousset, Raphael; Texier, Michael; Escoubas, Stéphanie; Dubourdieu, Catherine; Araújo, Eudes B. [UNESP]; Cornelius, Thomas W. (AIP Publishing, 2022)
The domain switching dynamics in a relaxor ferroelectric lanthanum-modified lead zirconate titanate thin film with 12 mol. % La was investigated by time-resolved x-ray diffraction. While most frequently epitaxial thin films are investigated, the present work reports results on a polycrystalline thin film. Asymmetric butterfly loops of the strain as a function of the applied electric field evidenced a built-in electric field oriented toward the thin film-substrate interface. The piezoelectric coefficient d33 (in the film reference frame) diminishes with the increasing frequency of an applied AC electric field. From the strain transient during the application of positive-up negative-down voltage pulse sequences with frequencies of up to 100 kHz, characteristic times of the order of 100-200 ns were determined for these relaxor ferroelectric thin films. While switching times ranging from the picosecond to the millisecond range are reported in the literature for different materials, these characteristic switching times are comparable to epitaxial lead zirconate titanate thin films of various compositions despite the polycrystallinity of the present thin film. However, the evidenced built-in electric field significantly influences the switching behavior for different polarities.